2010
DOI: 10.1002/pssb.201000305
|View full text |Cite
|
Sign up to set email alerts
|

Study of the mechanical response of carbon nanotubes‐SU8 composites by nanoindentation

Abstract: Multiwalled carbon nanotubes (MWCNTs)/SU8 composites have been produced to enhance the mechanical properties of SU8 photoresist. We have studied the influence of SU8 solvent on the structural homogeneity of composites through nanoindentation testing. It is found that acetone and propylene glycol methyl ether acetate (PGMEA) are very suitable solvents to prepare MWCNTs/SU8 composites with significant increase of the Young's modulus (E Y ). The highest increase of E Y in respect to the parent material of 104% wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Various CVD processes developed during the last three decades allow the formation of nano-scale structures. The relatively new processes include catalytic CVD [7], fluidized-bed CVD [8], rotary CVD [9], two-step (precursor vapor adsorption-decomposition) CVD [10] and large spot laser CVD [11]. To fabricate supported catalysts, the incorporation of active nanoparticles on high surface area porous supports is performed industrially by wet chemical methods including ion-exchange, co-precipitation, sol-gel, and wet impregnation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various CVD processes developed during the last three decades allow the formation of nano-scale structures. The relatively new processes include catalytic CVD [7], fluidized-bed CVD [8], rotary CVD [9], two-step (precursor vapor adsorption-decomposition) CVD [10] and large spot laser CVD [11]. To fabricate supported catalysts, the incorporation of active nanoparticles on high surface area porous supports is performed industrially by wet chemical methods including ion-exchange, co-precipitation, sol-gel, and wet impregnation.…”
Section: Introductionmentioning
confidence: 99%
“…Fluidized-bed chemical vapor deposition (FBCVD) is frequently employed for the incorporation of particles on the surface of sub-micron particles [12]. In addition, catalytic CVD (CCVD) and rotary reactor CVD are considered as the most suitable techniques for the large scale and low-cost production of single-or multi-walled carbon nanotubes (CNTs) [9,[12][13]. More recently, FBCVD is also being employed for the preparation of CNTs on active metal particles [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Other works involving solid nanoparticle addition to SU-8 have focused on the improvement of the bulk mechanical properties. For example, addition of 5 wt% of multiwalled carbon nanotubes in SU-8 has improved the Young's modulus by 104% measured in nanoindentation test [13]. In our previous works, we have reported that addition of liquid filler can be an excellent way to drastically reduce coefficient of friction and improve the wear life of SU-8 by the mechanism of in situ lubrication [14].…”
mentioning
confidence: 98%
“…A growing number of polymer based microdevices, mainly applied in microfluidics, can be found in the literature [1][2][3][4][5][6]. The growing interest in polymer based MEMS [7] has driven the development of novel processes and protocols to control its mechanical [8][9][10], optical [11], magnetic [12][13][14], and electrical [15][16][17] properties. Also the surface chemistry [18], the resolution attainable during optical lithography [19], and the topographical features were intensively studied.…”
Section: Introductionmentioning
confidence: 99%